Website content accessibility of the Cyprus domain - Zaphiris, Panayiotis; Zacharia, Giorgos (My University, 2003)
This paper extends previous studies that investigated the accessibility of different web sites of specific content, to an analysis of the whole web of a specific country (Cyprus). To our knowledge no previous study has analyzed such a big number of web sites for accessibility in a single study. More specifically this paper evaluates the compliance of 30,000 Cyprus related websites spidered by Arachne search engine. The 30,000 Cyprus related websites where evaluated for accessibility using the Bobby accessibility tool. Statistical analysis and comparison of the accessibility ratings for the different main domain categories (commercial, academic, governmental, and organizational) of the Cypriot web are also provided.